STUDI KOMPARATIF EFEKTIFITAS SKIPPING ROPE DAN PELATIHAN BEBAN DENGAN TEKNIK LEG PRESSTERHADAP PENINGKATAN DAYA LEDAK (POWER) OTOT TUNGKAI MAHASISWA PEMBINAAN PRESTASI BOLABASKET FOK (FAKULTAS OLAHRAGA DAN KESEHATAN) UNDIKSHA - I Kadek Happy Kardiawan (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
The research aims to know the different between the affectivity of skipping rope and the burden coaching by leg press technique toward the explosive power of leg muscle 30 students were taken as the population in this research. The dependent variable in this research is explosive power of leg muscle and the independent variable is skipping rope and burden coaching by leg press technique. The instrument used in this research was vertical jump test (Adisapoetra, dkk, 1999:59). The hypothesis test used in this research was independent samples t-test and paired samples t-test. The tests were done manually and by SPSS 10.0 for windows program.Based on the analysis result, it got that: first, there was a significant increasing in leg muscle explosive power from the result of pre-test to the result of post-test after giving leg press treatment. The mean of leg muscle explosive power from the post-test result (X = 64,73) was higher than the mean of leq muscle explosive power (X = 60,67) from the pre-test. Second, there was 2 significant increasing in leg muscle explosive power from the result of pre-test to the result of post-test after giving skipping rope treatment. The mean of leg muscle explosive power from the posttest result ( = 60,67) was higher than the mean of leg muscle explosive power from the pre-test ( = 48,67). Thfrd, there was a different in affectivity between skipping rope coaching and burden coaching with leg press technique toward the leg muscle explosive power. The mean of leg muscle explosive power in the leg press group(= 64,73) was higher than the mean of leg muscle explosive power in the skipping rope group(= 50,20). Keywords: leg muscle explosive power, skipping rope and burden coaching by leg press technique